(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2023)
Human Values and the Staff’s Recruitment in Social Assistance. The recruitment is a complicated and expensive process that has a strong impact on the organization. The efforts for the recruitment’s success have to be developed starting with the staff ’s resources prevision and scheduling and the analysis of posts to be occupied, too. If the staff ’s demand prevision calls for human resources need, then the organization will have to systematically recruit new employees. On the other hand, the recruitment has to focus on searching and attraction of trained staff. Thus, the recruitment’s success depends on how well is the vacant post defined. Incurious if the post is new or lay-off, its’ requirements have to be specified very precisely so that the recruitment to be efficient.